Plasma technique of carbon nanotube synthesis using commercial microwave oven - Nicodemus, Kure (2015)
Carbon nanotubes (CNTs) research have been the focus of revolutionizing nanotechnology, which stimulate attention from scientific communities to understand its exceptional properties, syntheses and potential applications such as sensor, field emission, hydrogen storage and biomedicine. Advances have been made by researchers, working extensively to develop diverse techniques such as arc discharge,laser ablation, thermal chemical vapor deposition and plasma enhanced chemical vapor deposition to synthesize CNTs, but these techniques are expensive and time consuming. The aim in this study is to develop a plasma technique using commercial microwave oven, to synthesize CNTs which can be more economical and less time consuming. The technique employed comprises of two parts; first part id to monitor the pressure level and plasma region while the second part deals with synthesis where require carbon source and catalyst are investigated. Commercial microwave oven with operating power of 600 W was used to irradiate the carbon source and coated substrate at atmospheric pressure with 2.45 GHz frequency, which leads to the formation of plasma in the tubular reactor. From the study shows that for CNTs growth, certain parameters are necessary to be controlled such as plasma, pressure at 0.81 mbar, temperature at 750 °C, catalyst (iron(III) nitrate nonahydrous), and carbon source (Polyethylene). The obtained CNTs were characterized via Raman spectroscopy which shows CNTs quality of 1.01, average tubes diameter at (6.0 to 10.0) ± 0.5 nm, twisted and oriented structures with interlayer spacing of about 0.35 nm and carbon purity of about 99.86%. The plasma technique results obtained shows that the technique is economical and fast process of synthesis.